Pengaruh Konsumsi Energi Listrik Kawasan Permukiman Terhadap Emisi Karbon Dioksida Kota Semarang - Tusiana Wismandani; Widjonarko Widjonarko (Teknik PWK (Perencanaan Wilayah Kota), 2017)
Population growth in Semarang City increases the need of settlements, which have many activities that need electricity power generated from the  power plant by burning a huge amount of fossil fuel. Carbon dioxide was a by-product of the burning process, and also the most abundant Green House Gas contained in the atmosphere. This research expected to dicover the influence of electricity consumption towards carbon dioxide   emissions   particularly   in   Semarang   City,   by   indetifying   the   electricity consumption of the four settlements sectors: household, industry, commercial, and governmental.  Then,  analyzing  their  correlation  and  effect  towards  carbon  dioxi de emissions partially using multiple regression method, and comprehensively using simple linear regression. The household sector has the highest electricity consumption, followed by industry, commercial, and governmental sector. Yet, it also has numerous consumers which caused it’s consumption per-consumer to be the lowest amongst all of the sectors. Conversely, industrial sector has the highest consumption per-consumer since it has high electricity usage yet a fewest consumers. The multiple regression analysis showed that sectoral electricity consumption didn’t represent a  valid  result because there  was  a multicollinearity between the independent variables. Whilst the simple regression discovered that comprehensive electricity consumption gave a significant effect to the carbon dioxide emissions, where 1% increasement of electricity usage also increase upto 1.421.525,52 ton carbon dioxide emissons.